2018
DOI: 10.1093/mnras/sty1872
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of neutral gas in centres of merging galaxies

Abstract: We present Giant Metrewave Radio Telescope and Very Large Array observations of H i 21-cm absorption in ten z 0.2 galaxy mergers that host strong radio sources. Seven of these mergers show strong absorption [with N (H i) ∼ 10 21−22 cm −2 , for spin temperature of 100 K and unit covering factor], leading to a total detection rate of 83 ± 17% in low-z radio-loud galaxy mergers. This is ∼ 3 − 4 times higher than that found for intrinsic H i 21-cm absorption in low-z radio sources in general. The fraction of intri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 125 publications
(166 reference statements)
6
22
0
Order By: Relevance
“…Earlier, a redshifted absorption with a similarly large velocity of 636 km s −1 relative to the AGN, was detected towards PKS 0428+20 at z = 0.219, by Vermeulen et al (2003). Recently, Dutta et al (2018) have also reported large velocity inflows in merging systems at z 0.2. Such large gas inflows could be explained in scenarios of galaxy mergers, wherein gas components get channelled to the central regions due to removal of angular momentum (e.g., Jogee 2006;Di Matteo et al 2008).…”
Section: Resultsmentioning
confidence: 88%
“…Earlier, a redshifted absorption with a similarly large velocity of 636 km s −1 relative to the AGN, was detected towards PKS 0428+20 at z = 0.219, by Vermeulen et al (2003). Recently, Dutta et al (2018) have also reported large velocity inflows in merging systems at z 0.2. Such large gas inflows could be explained in scenarios of galaxy mergers, wherein gas components get channelled to the central regions due to removal of angular momentum (e.g., Jogee 2006;Di Matteo et al 2008).…”
Section: Resultsmentioning
confidence: 88%
“…Remarkably, the optical depth estimated for the source J1209−2032 is one of the highest known for GPS and CSS sources. In a HI absorption study of galaxies with z > 0.2, Dutta et al (2018) reported that 40% of sources with column densities of HI > 10 21 cm −2 , and 100% of sources with HI > 10 22 cm −2 are associated with mergers. Also, the HI detection rate is high (∼80%) in merging systems.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the HI detection rate is high (∼80%) in merging systems. Dutta et al (2018) used SDSS images of galaxies to identify signatures of galaxy mergers. However, no evidence of a merger is found in the SDSS optical image of J1209−2032 (Sect.…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, the optical depth estimated for the source J1209−2032 is one of the highest known for GPS/CSS sources. In a HI absorption study of galaxies with z > 0.2, Dutta et al (2018) report that 40% of sources with column density, HI > 10 21 cm −2 and 100% of sources with HI > 10 22 cm −2 are associated with mergers. Also, the HI detection rate is high (∼80%) in merging systems.…”
Section: Discussionmentioning
confidence: 99%